Agent-based modeling and simulation in construction - Khodabandelu, Ali; Park, JeeWoong (Automation in construction, 2021)
Agent-based modeling (ABM) has gained popularity in construction research because of its unique system modeling features and recent advances in computing capabilities, leading to a significant growth in publication number on ABM construction research. To capture recent ABM development in construction research, this study conducts a three-step quantitative-qualitative review on 182 journal articles published between 2001 and 2020. Bibliometric and content analyses present metrics about publications, journals, and authors along with categorization of research studies. An integrated analysis combines the two preceding analyses to present an exhaustive discussion on research evolution and trends and identifies existing gaps and potential future research topics. The research can contribute to the body of knowledge from: 1) a theoretical perspective by further familiarizing researchers with ABM within the context of construction from a category-specific viewpoint; and 2) a practical perspective by reviewing industry-oriented studies and providing recommendations to raise their applicability in real construction. [Display omitted] •We conducted a quantitative-qualitative review on Agent-based modeling (ABM) applications in construction.•182 Journal articles published between 2001 and 2020 were analyzed in this exhaustive review.•We conducted a three-step quantitative-qualitative review: bibliometric, content, and integrated analyses•The analysis presents findings about publications, journals, and authors and research categorization•We discuss research growth and trends and identify existing gaps and potential future research topics